Do you see any problem? On the Developers Perceptions in Test Smells Detection - Lima, Rodrigo; Costa, Keila; Souza, Jairo; Teixeira, Leopoldo; Fonseca, Baldoino; D’Amorim, Marcelo; Ribeiro, Márcio; Miranda, Breno (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2023)
Developers are continuously implementing changes to meet demands coming from users. In the context of test-driven development, before any new code is added, a test case should be written to make sure new changes do not introduce bugs. During this process, developers and testers might adopt bad design choices, which may lead to the introduction of the so-called Test Smells in the code. Test Smells are bad solutions for implementing or designing test code. We perform a broader study to investigate the participants’ perceptions about the presence of Test Smells. We analyze whether certain factors related to the participant’ profiles concerning background and experience may influence their perception of Test Smells. Also, we analyze if the heuristics adopted by developers influence their perceptions about the existence of Test Smells. We analyze commits of open source projects to identify the introduction of Test Smells. Then, we conduct an empirical study with 25 participants that evaluate instances of 10 different smell types. For each Test Smell type, we analyze the agreement among participants, and we assess the influence of different factors on the participants’ evaluations. Altogether, more than 1250 evaluations were made. The results indicate that participants present a low agreement on detecting all 10 Test Smells types analyzed in our study. The results also suggest that factors related to background and experience do not have a consistent effect on the agreement among the participants. On the other hand, the results indicate that the agreement is consistently influenced by specific heuristics employed by participants. Our findings reveal that the participants detect Test Smells in significantly different ways. As a consequence, these findings introduce some questions concerning the results of previous studies that do not consider the different perceptions of participants on detecting Test Smells.